The Devaluation of the Naira and The State of the Nigerian Economy 1985 - 2015 (An Econometric Analysis) - Loto, Margaret Abiola (International Journal of Economics, Management and Accounting, 2018)
The paper investigated the impact of devaluation on the Nigerian economy from 1985–2016. Currency devaluation as a macroeconomic policy could have favorable as well as the unfavorable impact on any economy. The Nigerian government has demonstrated frequent implementation of this policy from 1986 till date, evidenced by the naira exchange rate to the dollar of between 450 and 480 naira at the time of this study. Hence, the need for a thorough examination of the impact (whether positive or negative) of currency devaluation on the Nigerian economy. To analyze the influence of devaluation as a policy on the Nigerian economy this study adopts the elasticity approach by using the import and export demand equation. The study used secondary time series data. For the analysis, Ordinary Least Squares (OLS) regression was adopted, with initial stationarity and stability tests. The result of the unit root test showed that the variables were of the same order of iteration being stationary at first difference. This gave room for the co-integration and error-correction tests. The overall result showed that even at this period, devaluation is yet to provide a solution for the Nigerian economy. This was because the sum of the relative prices of import and export coefficients stood at less than 1. This confirms again that devaluation is not the right policy for the Nigerian economy.